Awareness Of Applying Public Private Partnership (PPP) In Construction Industry Malaysia - Wee, Shu Jiuan (Universiti Sains Malaysia, 2006)
The use of the Public Private Partnership as procurement in delivery public infrastructure and services in Malaysia began active during the 1990s was much more rapid and widespread than had been expected at the start of the decade. However, these flows peaked in 1997, and have fallen more or less steadily ever since because a variety of problems have been encountered and the financial crisis in the region. These declines have been accompanied by cancellations or renegotiations of some projects, a reduction in investor’s interest and pursue for the public infrastructure and services. However, the needs for infrastructure are now greater than ever in emerging and developing countries such as Malaysia. Both government and private sectors are recommending and trying to apply these types of approach for the reasons of it is the best solution to solve the government’s problems.